170k views
5 votes
M is the midpoint . LM = x+9 MN = 4x find the length of LN

1 Answer

0 votes

Explanation:

MN=x+16

MN=x+16LN=4x+16

MN=x+16LN=4x+16LM+MN=LN

MN=x+16LN=4x+16LM+MN=LNLM+(x+16)=4x+16

MN=x+16LN=4x+16LM+MN=LNLM+(x+16)=4x+16LM=(4x+16)-(x+16)

MN=x+16LN=4x+16LM+MN=LNLM+(x+16)=4x+16LM=(4x+16)-(x+16)LM=4x+16-x-16

MN=x+16LN=4x+16LM+MN=LNLM+(x+16)=4x+16LM=(4x+16)-(x+16)LM=4x+16-x-16LM=3x

MN=x+16LN=4x+16LM+MN=LNLM+(x+16)=4x+16LM=(4x+16)-(x+16)LM=4x+16-x-16LM=3x

MN=x+16LN=4x+16LM+MN=LNLM+(x+16)=4x+16LM=(4x+16)-(x+16)LM=4x+16-x-16LM=3x 3x=x+16 3x-x=16 2x=16 x=16/2 x=8 MN=x+16=8+16=24

User Jarrod Funnell
by
4.6k points